Electrohydrodynamic (EHD) bioprinting of polycaprolactone scaffolds - (:unkn) unknown (Trans Tech Publications Ltd, 2018)
This study is combined a 3D printing and Electrohydrodynamic (EHD) methods to fabricate a 3D PCL scaffolds for tissue engineering. Various kV values were applied to the different PCL solutions to investigate the effect of the voltage on scaffolds. The morphology of 3D-EHD printed PCL scaffolds were characterized by an Optical Microscope. 10 wt.% PCL up to 3 kV was obtained best sample to use for tissue engineering scaffolds. © 2018 Trans Tech Publications, Switzerland.
Keywords: Bioprinting; EHD; Polycaprolactone; Tissue engineering